2000
DOI: 10.1080/026520300420439
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydro-beta-carboline-3-carboxylic acid compounds in fish and meat: possible precursors of co-mutagenic beta-carbolines norharman and harman in cooked foods

Abstract: The presence of tetrahydro-beta-carbolines and beta-carbolines was studied in raw, cooked and smoked fish and meat. 1,2,3,4-Tetrahydro-beta-carboline-3-carboxylic acid (THCA) usually was the major beta-carboline found, whereas 1-methyl-1,2,3,4-tetrahydro-beta-carboline-3-carboxylic acid (MTCA) appeared in smoked and 'well done' cooked samples. THCA was detected in raw fish (nd-2.52 micrograms/g), cooked fish (nd-6.43 micrograms/g), cooked meats (nd-0.036 microgram/g), smoked fish (0.19-0.67 microgram/g) and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 34 publications
5
61
0
Order By: Relevance
“…From these studies, it was concluded that high-temperature preparation procedures resulted in the highest levels of HCA including norharman and harman. This was also confirmed in other studies with different food items such as beef or fish [26]. Irrespective of the meat type grilling on an open flame resulted in extremely high levels of norharman and harman [65] (Table 1).…”
Section: β-Carbolines In Foodsupporting
confidence: 83%
See 3 more Smart Citations
“…From these studies, it was concluded that high-temperature preparation procedures resulted in the highest levels of HCA including norharman and harman. This was also confirmed in other studies with different food items such as beef or fish [26]. Irrespective of the meat type grilling on an open flame resulted in extremely high levels of norharman and harman [65] (Table 1).…”
Section: β-Carbolines In Foodsupporting
confidence: 83%
“…In addition to intake of norharman and harman, ingestion of precursors may further result in elevated plasma levels of ␤-carbolines, this has been shown for l-tryptophan [78]. It may be hypothesised that dihydro-and tetrahydro-derivatives of ␤-carbolines, ingested with fried food at ppm levels [26] may be transformed in vivo into norharman and harman.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Besides the fermented foodstuffs, β-carbolin derivatives are also present in raw, cooked and smoked fish and meat, and they are possible chemical precursors of the co-mutagens norharman and harman [20]. Therefore, toxicological aspects of fermented garlic will be further studied.…”
Section: Resultsmentioning
confidence: 98%